1999
DOI: 10.1021/bi991064t
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Steady-State Kinetic Investigation of Intermediates in the Reaction Catalyzed by Adenosylcobalamin-Dependent Glutamate Mutase

Abstract: Glutamate mutase catalyzes the reversible isomerization of L-glutamate to L-threo-3-methylaspartate. Rapid quench experiments have been performed to measure apparent rate constants for several chemical steps in the reaction. The formation of substrate radicals when the enzyme was reacted with either glutamate or methylaspartate was examined by measuring the rate at which 5'-deoxyadenosine was formed, and shown to be sufficiently fast for this step to be kinetically competent. Furthermore, the apparent rate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 24 publications
5
59
0
Order By: Relevance
“…The 5'-dA formed in the reaction was recovered by reverse-phase HPLC. [26] The deuterium content of the 5'-dA was determined by ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS). The 5'-dA isolated from the reaction contains a mixture of isotopomers, with contributions from natural abundance 13 C, 15 N, 17 O, and 2 H isotopes in addition to any deuterium from the substrate.…”
mentioning
confidence: 99%
“…The 5'-dA formed in the reaction was recovered by reverse-phase HPLC. [26] The deuterium content of the 5'-dA was determined by ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS). The 5'-dA isolated from the reaction contains a mixture of isotopomers, with contributions from natural abundance 13 C, 15 N, 17 O, and 2 H isotopes in addition to any deuterium from the substrate.…”
mentioning
confidence: 99%
“…Many researchers have considered axial ligand transinfl uence, steric effects, structural strain, protein infl uence, in addition to others [47][48][49][50][51][52][53][54][55][56][57][58] as determinant factors in the Co-C cleavage process. The hydrogen transfer from the substrate to 5-deoxysdenosyl ligand has also been considered as a triggering factor of the Co-C bond breaking [59][60][61][62][63][64][65][66][67]. These suggestions have been largely unconfi rmed by subsequent data.…”
Section: The Mechanisms Of Methylcobalamin and Adenosylcobalamin Actimentioning
confidence: 99%
“…This suggests that a step other than hydrogen transfer is partially rate limiting in the overall reaction. Rapid quench experiments have allowed the pre-steady-state kinetics of product formation to be examined and have shown that product release is not rate limiting in either direction (40). As discussed below, this leaves the rearrangement of the substrate radical as a relatively slow step responsible for the suppression of the isotope effects.…”
Section: Figmentioning
confidence: 99%